การเตรียมอนุภาคระดับนาโนของซิลิกา/พอลิเมทิลเมทาคริเลตคอมพอสิตผ่านการเกิดพอลิเมอร์แบบดิฟเฟอเรนเชียลไมโครอิมัลชัน - ศรีสุดา ศรีดาว (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This research aimed to prepare silica (SiO2)/poly(methyl methacrylate) (PMMA) composite nanoparticles via in situ differential microemulsion polymerization process. Sodium dodecyl sulfate (SDS) and 2,2 azobis (isobutyronitrile) (AIBN) were used as an anionic surfactant and oil soluble initatior, respectively. The methyl methacrylate monomer feed into the reactor was provided in very small drops and the time interval between drops was very short. The weight ratio of the surfactant/methyl methacrylate monomer was as low as 1/70. Nano-SiO2 particles were first treated with 3-methacryloxypropyl trimethoxysilane (MPTMS) coupling agent to improve the particle-PMMA interfactial adhesion. The obtained composite nanoparticles were investigated for their particle size, %yield and morphology. The results showed that the nanocomposite particles had an average particle size about 40 nm. As much as 49-66% by weight of PMMA was coated on the silica surface depend on the amount of the pretreated nano-SiO2 in the differential microemulsion system.